Evaluating insecticide susceptibility in major African malaria vectors: a meta-analysis and systematic review - Minwuyelet, Awoke; Yewhalaw, Delenasaw; Sciarretta, Andrea; Atenafu, Getnet (Frontiers in Malaria, 2025)
BackgroundAfrica is still home to the highest number of malaria cases and deaths. To reduce the burden of malaria in Africa, different classes of insecticides have been used since the eradication era. However, the effectiveness of insecticides is reduced periodically. This study aimed to assess the susceptibility status of major African malaria vectors to different insecticides commonly used for public health.MethodsTo conduct this review, we used open-access global databases, i.e., PubMed, Google Scholar, Scopus, Web of Sciences, and Pro-Quest, to extract relevant articles published between January 2002 and 28 December 2023. Primary articles were searched using keywords such as “insecticide susceptibility status”, ‘insecticide resistance”,” malaria vectors”, “Africa”, and “Anopheles”. Articles published in English that met the inclusion criteria were included in this review. Data were extracted from the included article texts, tables, figures, and supplementary information. The validity of all included articles was checked before inclusion by critical evaluation using standardized methods. Finally, the results of the original articles are presented in tables, graphs, and maps.ResultsIn total, 61 relevant articles were retrieved and extracted from 1,794 accessed articles. Of these, most articles documented resistance in Anopheles gambiae s.l. and An. funestus to organochlorines, i.e., DDT (4%); cyclodins, i.e., dieldrin (4%); pyrethroids, including lambda-cyhalothrin (0.05%), cyfluthrin (0.15%), permethrin (0.75%), and deltamethrin (0.05%); and carbamate, i.e., propoxur (0.1%), across Africa. These mosquito species have also developed knockdown resistance to different insecticide classes (pyrethroids and organochlorines) in Africa. However, the resistance of these malaria vectors varied in different areas of the continent and in different localities within the same country. The highest levels of insecticide resistance in Anopheles mosquitoes across Africa were recorded between 2011 and 2015. However, currently, mosquito populations are susceptible to candidate insecticides such as chlothianidin (neoncotinoid), chlorfenapyr (pyrole), and brofanilide (meta-diamide), which are newly introduced insecticides for vector control interventions.ConclusionThis review revealed that the major African malaria vectors have developed resistance to most insecticides used for public health. However, they were susceptible to a few existing insecticides (pirimiphos-methyl) and new candidate insecticides such as clothianidin, chlorfenapyr, and brofanilide. This warrants the development and implementation of insecticide resistance monitoring and management strategies for malaria control and elimination programs in malaria endemic countries of Africa to extend the effective lifespan of insecticides to which populations of the major African malaria vectors are susceptible and to reduce the resistance frequency. We also recommend the use of integrated vector management to complement the chemical insecticide vector control interventions in the containment of major African malaria vectors.